2021
DOI: 10.3390/jcm10225307
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Specific Antigen and Testosterone Levels as Biochemical Indicators of Cognitive Function in Prostate Cancer Survivors and the Role of Diabetes

Abstract: Prostate cancer (PC) is one of the most common malignancies in men. The increase in the number of PC survivors is associated with many problems including cognitive impairment. Early detection of such problems facilitates timely protective intervention. This study examined the association between prostate-specific antigen (PSA) or testosterone (T) levels and cognitive function in patients undergoing radical prostatectomy. Such a correlation could help identify patient groups at risk of cognitive impairment. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…A study from Japan of older men found that higher salivary testosterone concentration measured by immunoassay was associated with better global cognitive function [75]. In a study of prostate cancer patients from Poland, higher testosterone levels in those who had received ADT were associated with better cognitive function based on neuropsychological assessment [76]. These findings support the influence of androgens such as testosterone on cognitive function and the potential of cognitive disruption with anti-androgen treatment.…”
Section: Testosterone Impact On Cognition Mood and Energymentioning
confidence: 85%
“…A study from Japan of older men found that higher salivary testosterone concentration measured by immunoassay was associated with better global cognitive function [75]. In a study of prostate cancer patients from Poland, higher testosterone levels in those who had received ADT were associated with better cognitive function based on neuropsychological assessment [76]. These findings support the influence of androgens such as testosterone on cognitive function and the potential of cognitive disruption with anti-androgen treatment.…”
Section: Testosterone Impact On Cognition Mood and Energymentioning
confidence: 85%
“…Markers in the region of EFNA1, DPM3, SLC50A1 have previously been associated with prostate cancer risk 16 . Prostate cancer risk on the other side correlates with serum testosterone levels 17 . All of these observations suggest a possible gene-environmental interaction for this region.…”
Section: Discussionmentioning
confidence: 99%